How Early Career Choices Adjust to Economic Crises - Julien Grenet; Hans Grönqvist; Edvin Hertegård; Martin Nybom; Jan Stuhler (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
We study how students adjust their early career choices in response to economic crises and how these decisions affect their long-run labor market outcomes. Focusing on Sweden's deep recession in the early 1990s—which hit the manufacturing and construction sectors hardest—we first show that students whose fathers lost jobs in these sectors were more likely to choose career paths tied to less-affected industries. These students later experienced better labor market outcomes, including higher employment and earnings. Our findings suggest that informational frictions are a key obstacle to structural change and identify career choice as an important channel through which recessions reshape labor markets in the long run.
Keywords: I25; J24; J63; E32; 330; high school major; recession; information frictions; structural change